CAMP-PKA signaling is involved in regulation of spinal HCN channels function in diabetic neuropathic pain. (17th April 2021) - Ma, Yanqiao; Chen, Ji; Yu, Deqian; Wei, Bangcong; Jin, Huan; Zeng, Junwei; Liu, Xiaohong
Highlights: Diabetic neuropathic pain increases the expression of spinal HCN2, 4, PKA and the formation of cAMP. Inhibition of cAMP and PKA reduces the expression of spinal HCN2 and HCN4 channels. Blockade of HCN channels by ZD7288 decreases spinal cAMP levels and PKA protein expression. Abstract: The cyclic adenosine monophosphate-protein kinase A (cAMP-PKA) signaling acts a pivotal part in hyperpolarization-activated cyclic nucleotide-gated (HCN) channels-mediated neuropathic and inflammatory pain. However, there has been no evidence of cAMP-PKA signaling is involved in regulation of spinal HCN channels function in the occurrence of diabetic neuropathic pain (DNP). The study aimed to elucidate the impact of HCN channels on neuropathic pain in a rat model of diabetes induced by streptozotocin, and whether cAMP-PKA signaling is involved in regulation of HCN channels function. In this report, we evaluated the effect of intrathecal administration of HCN channel blockers ZD7288, cAMP inhibitor SQ22536 and PKA inhibitor H-89 on nociceptive behavior in DNP rats. The mechanical withdrawal threshold (MWT) was measured to evaluate pain behavior in rats. Protein expression levels of HCN2, HCN4 channels and PKA in the spinal dorsal horn of rats were assessed. Furthermore, the levels of cAMP in rat spinal dorsal horn was analyzed. We discovered that DNP rats showed significant mechanical allodynia and are related to the increased HCN2 and HCN4 channels expression, enhanced cAMP production and elevated the expression of PKA protein in the spinal dorsal horn, which were attenuated by intrathecal ZD7288. Furthermore, intrathecal injection of SQ22536 and H-89 significantly reduced the HCN2 and HCN4 channels expression in the spinal dorsal horn of DNP rats. Our findings indicate that HCN channels of the spinal dorsal horn participate in the pathogenesis of allodynia in rats with DNP, which could be regulated by cAMP-PKA signaling. Therefore, HCN channels and cAMP-PKA signaling are potential targets for hyperalgesia treatment in DNP patients.